Design of thin circular polarization selective surface - Cao, Yibo (Nanyang Technological University, 2024)
As a special spatial filter, CPSS has different polarization selective characteristics for different types of circular polarization waves operating at the same frequency and has been widely used in the design of wireless communication systems recently. Exploring new and thinner CPSS structure has certain research value for antenna design. In this dissertation, the coupling effect and the bending separation of the conductive section are used to achieve the miniaturization and thickness reduction of the CPSS structure, and some technical improvements and innovative means are made. The influence of different coupling types and CPSS with different bending section lengths on the performance is proposed and compared. The specific research contents are as follows: After extensive reading and research of CPSS structures proposed so far, the optimization methods and performance comparison of different CPSS structures are summarized, and the popular thickness optimization methods are analyzed. The traditional Pierrot model element is simulated and reduced, and the proposed three-layer thin CPSS design structure is simulated and verified by replacing the vertical conductive section with coupled L-shaped polyline. According to the working principle of the traditional Pierrot unit, a thin CPSS based on the bent coupling line is designed in this dissertation. Based on the principle of surface current, the designed model is simulated and verified, and the working frequency is 12 GHz. The optimized CPSS structure thickness is reduced from 0.25〖 λ〗_c (9.375mm) to 0.21λ_c (5.36mm). The simulation results show that at the operating frequency of 12 GHz, the 3 dB resonance bandwidth and 3 dB AR bandwidth of LHCP wave are 24.7% and 29.17% respectively. And the length is adjusted and optimized to reduce the thickness again from 0.21λ_cto 0.19λ_c(4.74mm), the reflection and transmission performance of the whole structure is not much attenuation, but the AR bandwidth is reduced to 24.1%, and the cross-polarization frequency is slightly deviated from the operating frequency.